EVALUATION OF THE COMPLETENESS OF ELECTRONIC MEDICAL RECORDS IN HYPERTENSION PATIENTS AT UPTD PUSKESMAS KINTAMANI V - Ni Wayan Anik Linda Yani; Nurul Faidah; Ni Nyoman Meryadi (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
Electronic medical records are an important part of the implementation of health services in community health centers because they function as a source of information regarding patient identity, examinations, treatments, actions, and other services that have been provided to patients. This study aims to determine the evaluation of the completeness of electronic medical records in hypertension patients at UPTD Puskesmas Kintamani V. This study used a descriptive research design with a quantitative approach. The sample consisted of 149 electronic medical records of hypertension patients selected using the total sampling technique. Data were collected using an observation checklist based on the components of identification review, important reports, authentication, and proper documentation. The data analysis technique used univariate analysis. The results showed that the average completeness of patient identification was 92.53%, with components that were 100% complete including medical record number, patient name, gender, and phone number, while the completeness of the National Identification Number (NIK) was 89.3%, address 80.5%, and place/date of birth 77.9%. In addition, there were components not available in the system, namely religion, marital status, and occupation (100%). The review of important reports showed an average completeness of 99.43%, with incompleteness in the e-prescription component of 3.4%. The authentication and proper documentation components showed 100% completeness.